LITERASI LINGKUNGAN BAGI ANAK-ANAK DI DANAU SENTANI, PAPUA - Henderite L.Ohee; Wigati Yektiningtyas; Stela R. Korwa; Christien S. A. Haay (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Lake Sentani has significantly changed in the last twenty years. These changes are due to various human activities that cause habitat loss and changes of fish communities in the lake. It could have impact the local community knowledge on Sentani Lake, particularly for children. Therefore, it is important to equip children with enough environmental literacy about Lake Sentani so that they understand the need to protect and conserve the lake. To achieve that, the community service targetting children was carried out with children from Yokiwa Traditional Village in Jayapura regency in the library of “Snaggar Napas Danau Sentani’s Studio. The activity was conducted for eight months, from May to December 2022. Five activities has been running with children in Yokiwa Traditional Village from July to October 2022, while other programs are carried out outside the village and the output is reported to partner. Information on Lake Sentani and its fish species has been shared to these children. The N-Gain test found that the children's knowledge about Lake Sentani was low. Environmental literacy about Lake Sentani needs to continually reshare to children in this village as well as to other children in villages around Lake Sentani. Abstrak Danau Sentani mengalami perubahan yang signifikan dua puluh tahun terakhir. Perubahan tersebut akibat berbagai aktivitas manusia yang menyebabkan hilangnya habitat dan berubahnya komunitas ikan di danau. Perubahan tersebut dapat menyebabkan perubahan pengetahuan pada masyarakat lokal khususnya anak-anak. Oleh karena itu literasi lingkungan tentang Danau Sentani penting untuk diberikan kepada anak-anak agar mereka tahu tentang Danau Sentani. Untuk itu pengabdian ini dilaksanakan khususnya kepada anak-anak komunitas Perpustakaan Kampung Sanggar Napas Danau Sentani di Kampung Adat Yokiwa, Kabupaten Jayapura, Papua. Pengabdian dilaksanakan selama delapan bulan, Mei-Desember 2022. Lima kegiatan dilaksanakan bersama anak-anak di Kampung Adat Yokiwa, Juli-Oktober 2022, sedangkan program-program lain dilaksanakan di luar lokasi pengabdian dan luarannya diberikan kepada mitra. Pengetahuan tentang Danau Sentani dan jenis-jenis ikan diajarkan kepada anak. Uji N-Gain mendapatkan bahwa pengetahuan anak-anak tentang Danau Sentani rendah. Literasi lingkungan tentang Danau Sentani perlu dilakukan kembali di komunitas, juga kepada lebih banyak anak-anak di Danau Sentani.